Retinal changes in Parkinson's disease and glaucoma. (November 2018) - Matlach, Juliane; Wagner, Martin; Malzahn, Uwe; Schmidtmann, Irene; Steigerwald, Frank; Musacchio, Thomas; Volkmann, Jens; Grehn, Franz; Göbel, Winfried; Klebe, Stephan
Abstract: Background: The topic of retinal neurodegeneration in PD is controversial, therefore the objective was to compare macular ganglion cell complex (mGCC) and peripapillary retinal nerve fiber layer (pRNFL) thickness in PD using 2 Spectral-Domain (SD) Optical Coherence Tomography (OCT) devices. Methods: In total, 146 eyes of 130 age-similar patients were included, of these 46 eyes of 30 PD patients, 60 eyes of 60 glaucoma patients and 40 eyes of 40 healthy controls. Peripapillary RNFL and mGCC were measured. Correlation analyses were performed for evaluation of association between pRNFL or mGCC and PD severity using the Movement Disorder Society (MDS)-Unified Parkinson Disease Rating Scale (UPDRS). Scatterplots were used to evaluate relationships between disease duration, dopamine dose, olfactory assessment and retinal thickness. Results: No significant difference was found for both eyes of PD patients compared to healthy subjects neither for overall mGCC nor each sector. However, the ipsilateral eye to the most-affected body side with bradykinesia in PD patients had a statistically significant thinner superior pRNFL compared to healthy controls (P = 0.03). There was no significant correlation between pRNFL or mGCC and disease severity; also, the scatterplots did not indicate a correlation between disease duration, dopamine dose, olfactory testing and OCT results. Conclusions: Imaging of the retina revealed thinning of some retinal layers of the ipsilateral eye to the most-affected body side in PD patients compared to healthy controls. Peripapillary RNFL and mGCC did not correlate to disease severity; however, this was a fairly small and heterogeneous group of PD patients. Highlights: Comparison of retinal morphology in Parkinson's disease, glaucoma and healthy controls using OCT retinal imaging. Imaging of macular retinal layers did not reveal changes in macular inner retinal thickness in PD patients. IpRNFL of the ipsilateral eye to the most-affected body side with bradykinesia was slightly thinner in PD patients. Macular inner retinal thickness and pRNFL measurement did not prove to be a diagnostic biomarker of neurodegeneration in PD.